Risk factors and outcomes of inpatients with carbapenem-resistant Pseudomonas aeruginosa bloodstream infections in China: a 9-year trend and multicenter cohort study - Yuan, Qing; Guo, Lei; Li, Bin; Zhang, Sheng; Feng, Haiting; Zhang, Yan; Yu, Meihong; Hu, Hangbin; Chen, Hongchao; Yang, Qing; Qu, Tingting (Frontiers in Microbiology, 2023)
Objective: Bacteremia caused by carbapenem-resistant Pseudomonas aeruginosa (CRPA) has high mortality, threatening the healthcare quality worldwide. Analysis is required to update the epidemiological data of CRPA bloodstream infections (BSI) and evaluate the prevalent strains in China. Moreover, it is necessary to clarify the risk factors associated with the development and mortality of CRPA bacteremia. Methods: This is a 9-year multicenter retrospective study, enrolling 137 patients with CRPA BSI and 137 carbapenem-susceptible P. aeruginosa (CSPA) BSI during January 2012 and December 2020. Antimicrobials susceptibility between the two groups were compared. Risk factors of CRPA BSI were identified by binary logistic regression for development and cox regression for mortality. The Kaplan-Meier method was used to compare time to mortality. CRPA and difficult-to-treat resistant P. aeruginosa (DTRPA) detection rate was analyzed year-by-year in ZYH. Results: A total of 7,384 P. aeruginosa clinical samples were cultured in ZYH during 9 years, and notable increase of CRPA and DTRPA detection rate in P. aeruginosa BSI was identified (from 17% to 60%; from 2.1% to 25%). Multivariate analysis revealed that prior ICU hospitalization, immunosuppressive therapy and exposure to carbapenems were independent risk factors for development of CRPA BSI. The 30-day crude mortality of 137 CRPA BSI was 39%. A total of 46 DTRPA were identified, and the 30-day mortality for patients infected by DTRPA was 50%. The 30-day crude mortality of CRPA BSI was independently associated with multiple organ failure and higher Pitt bacteremia score, whereas receipt appropriate therapy improved prognosis. Conclusion: A significant increase in the detection rate of CRPA and DTRPA in P. aeruginosa BSI was identified. Strict policies for carbapenems usage, cautious decisions regarding the usage of immunosuppressive agent and standard care for patients with prior ICU hospitalization are necessary for CRPA BSI management.